FURTHER OBSERVATIONS ON METACESTODIOSIS IN BLACK BENGAL GOAT IN BANGLADESH (Biological Sciences - PJSIR, 2002)
Examination of 430 slaughtered Black Bengal goats, 198 male and 232 female,between 1 to 2.5 years of age, revealed 210 (48.84%) Cysticercus tenuicollis, 31 (7.21%) Coenurus cerebra/is and  5 (1.16%) mixed infection  with  C. tenuicollis  and• cerebra/is, while none of the goats had hydatid infection. The rate of infection was significantly (p